Bail-in and Legacy Assets: Harmonized rules for targeted partial compensation to strengthen the bail-in regime - Philipp Poyntner; Thomas Reininger (Oesterreichische Nationalbank (OeNB), 2018)
In the wake of the global financial crisis, several large bank rescues by governments further entrenched bail-out expectations in the wider public. Then, following a problematic ad-hoc bail-in in Cyprus early 2013, EU rules introduced provisions for 'bail-in', that is, the administrative power to require write-down or conversion into equity of non-equity claims – a significant regime change to deal with banks failing or likely to fail. This paper focuses on the implications of this regime change for consumer/investor protection, especially for socially more vulnerable households, and on the resulting risk for political acceptance and the achievement of the bail-in objective. Therefore, it reviews these rules and their application in recent cases, focusing on the treatment of retail bond holders. Moreover, it explores the distribution of retail holders of bank bonds across economy-wide income quantiles in the euro area and various euro area countries. We find that neither the share of below-medianincome households with bank bonds in the total number of households with bank bonds nor the relative vulnerability to 'bail-in' of these households that tend to have higher levels of financial illiterateness are negligible. Recent applications of bail-in-rules, while diverse with respect to legal basis, scope and purpose, have barely gone beyond the write-down and conversion of capital instruments, thus excluding senior bonds. Nevertheless, in all these cases, some sort of compensation scheme for retail investors was deemed necessary and implemented, varying in design, but mostly benefiting almost all retail holders. In two prominent cases there was no effective bail-in of retail holders. In conclusion, following a lesser-known example from Italy, we propose EU harmonized partial compensation rules for socially more vulnerable retail holders of bank debt securities acquired before 2016. They would render implementation of bail-in socially more acceptable, politically more feasible and economically more efficient. During the transition period until household investment behaviour will have fully adjusted to the new world of bail-in, the proposed compensation rules would help avoid effective non-application of bail-in that otherwise results from excluding senior bonds and/or granting excessive compensation.
Keywords: D14; D18; D31; D63; E44; G21; G28; H81; 330; banking regulation; bail-in; retail holders; consumer protection; income